The effect of health insurance coverage on antenatal care utilizations in Ethiopia: evidence from national survey - Merga, Bedasa Taye; Raru, Temam Beshir; Deressa, Alemayehu; Regassa, Lemma Demissie; Gamachu, Mulugeta; Negash, Belay; Birhanu, Abdi; Turi, Ebisa; Ayana, Galana Mamo (Frontiers in Health Services, 2023)
Background About three-fourths of maternal near-miss events and two-fifths of the risk of neonatal mortality can be reduced by having at least one antenatal visit. Several studies have identified potential factors related to maternal health seeking behavior. However, the association between health insurance membership and antenatal care utilization was not well investigated in Ethiopia. Therefore, this study was aimed at assessing the effect of health insurance coverage on antenatal care use in Ethiopia. Methods The study utilized data from the 2019 Ethiopia Mini Demographic and Health Survey (EMDHS). The analysis included a weighted sample of 3,919 women who gave birth in the last five years. A logistic regression model was employed to assess the association between antenatal care use and health insurance coverage and other covariates. The results were presented as adjusted odds ratios (AOR) at a 95% confidence interval (CI). Statistical significance was declared at a p-value <0.05 in all analyses. Results Antenatal care was used by 43% (95% CI: 41.46 to 44.56%) of Ethiopian women. Those with health insurance coverage had higher odds of antenatal care use than those without health insurance coverage. Women were 33% more likely to use antenatal care (ANC) if they were covered by health insurance. Age, Media access, marital status, education status, wealth index, and economic regions were also factors associated with antenatal care utilizations. Conclusions According to our findings, less than half of Ethiopian women had four or more antenatal care visits. Health insurance membership, respondent age, media access, marital status, education status, wealth index, and economic region were factors associated with antenatal care utilization. Improving health insurance, women's economic empowerment, and education coverage are critical determinants of antenatal care utilization.